2019
DOI: 10.1161/hypertensionaha.118.12766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Walnut Diet on Office and 24-Hour Ambulatory Blood Pressure in Elderly Individuals

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 33 publications
3
24
1
1
Order By: Relevance
“…The results of our study indicated that supplementing the diet of older adults with a daily dose of walnuts and no other dietary advice for two years resulted in neither an adverse effect on development of MetS nor its reversion. Even so, we observed a trend towards a beneficial effect of walnut consumption on blood pressure, a finding that has been reported in previous nut studies [11,[31][32][33][34]. The results from the same WAHA feeding trial confirmed the favorable effects of walnut consumption in lowering blood pressure [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of our study indicated that supplementing the diet of older adults with a daily dose of walnuts and no other dietary advice for two years resulted in neither an adverse effect on development of MetS nor its reversion. Even so, we observed a trend towards a beneficial effect of walnut consumption on blood pressure, a finding that has been reported in previous nut studies [11,[31][32][33][34]. The results from the same WAHA feeding trial confirmed the favorable effects of walnut consumption in lowering blood pressure [31].…”
Section: Discussionsupporting
confidence: 89%
“…Even so, we observed a trend towards a beneficial effect of walnut consumption on blood pressure, a finding that has been reported in previous nut studies [11,[31][32][33][34]. The results from the same WAHA feeding trial confirmed the favorable effects of walnut consumption in lowering blood pressure [31]. Other trials have also shown a decrease in blood pressure when consuming a Mediterranean diet (MedDiet) supplemented with 30 g/d of mixed nuts (walnuts 15g, hazelnuts 7.5g, and almonds 7.5g) [11,32].…”
Section: Discussionsupporting
confidence: 87%
“…Numerous randomized studies have reported that diets enriched with nuts consistently reduced blood pressure [29,30] and LDL cholesterol [31,32]. The effects of a nut-rich diet on HDL cholesterol have varied among studies, although the relationship between total cholesterol and HDL cholesterol usually decreases [33].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a meta-analysis, that study [ 65 ] may have had a few limitations due to heterogeneity. The results of Domènech et al [ 63 ] provide what appears to be reliable evidence, based mainly on its long-term duration and sample size.…”
Section: Alternative Plant Sources Of N3-pufasmentioning
confidence: 95%
“…Walnuts are an important source of ALA [ 61 , 62 ]. A 2-years follow-up study recruited 236 elderly subjects, segregated into two groups: a control group without nut consumption, and an intervention group in which 15% of the approximate daily energy intake consisted of walnuts, at approximately 30–60 g/day of walnuts [ 63 ]. The researchers found a reduction of 8.5 mmHg in the systolic blood pressure, whose baseline levels were >125 mmHg; however, no changes were observed in diastolic blood pressure.…”
Section: Alternative Plant Sources Of N3-pufasmentioning
confidence: 99%